The relationship between man and nature in Ibn Khaldun’s muqaddimah - Ren, Huichan; Suhaila Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Ibn Khaldun, one of the most prominent Muslim social scientists of the Middle Ages, is famed for his historical ideas and unique insights into the emergence and collapse of civilisations. This study aims to explore the relationship between man and nature in light of Ibn Khaldun’s greatest work, The Muqaddimah. A vast number of scholars have examined human civilisation from various perspectives as expounded in the Muqaddimah but works dedicated to the relationship between man and nature are still few. As a result, this article investigates Ibn Khaldun’s view of the relationship between man and nature through a qualitative content analysis of the Muqaddimah. Since Ibn Khaldun was a great Muslim thinker who had a deep effect on the Muslim world, his concept of the relationship between man and nature is readily accepted by Muslims and may play a constructive role in environmental conservation in the Muslim world. After reading and analysing the Muqaddimah, this article concluded that Ibn Khaldun’s examination of the link between man and nature can be found in every chapter. He thinks that the environment has a significant impact on individuals and human civilisation, as well as he advocates that man should respect nature and utilize it rationally to sustain civilisation’s healthy development.